PSYCHOLOGICAL WARFARE AND MILITARY SCIENCES (Heritage, 2021)
In this paper the brief development and contemporary trends in modern military psychology, in theory and praxis, were presented. The origins and concepts of psychological warfare and its basic characteristics were discussed. Also, simmilar terms, modified with conceptual frameworks and contemporary development of military sciences, like special warfare, hybrid warfare, asymmetric warfare, cyber warfare, low-intensity conflict, public diplomacy, total warfare, were disucssed.The development of modern weapons and technologies brings changes in the perception of importance of psychological warfare of itself, but also different possibilities of use of modern techniques in it. The special opportunity presents social networks, characterized by hugh speed, wide spread network, different modes, adaptibility, avaliability and simplicity of use. All these changes also broght some changes in definition of psychological warfare inside military psychology of itself, but also changes the definition of perception of terms and modus of war, so as the polity of the states, geopolitical situation and gobal economy.
Keywords: colour revolution, military psychology, warfare